Use of Glycopyrrolate to Treat Intraoperative Penile Erection: Case Report and Review of the Literature. Issue 6 (November 1994) - Valley, Marc A.; Sang, Christine N.
Abstract : Background and Objectives: Penile erections following the initiation of either axial regional or general anesthesia is rare; however, when it occurs in patients undergoing urologic procedures it may delay, or even cancel, the planned surgery. The purpose of this case report and review is to enhance anesthesiologists' understanding of this phenomenon so that they may better formulate a logical treatment scheme in such an event. Methods: We present a case of intraoperative erection after the initiation of continuous spinal anesthesia that was treated with intravenous glycopyrrolate. From the literature, 72 references were reviewed. Results: Glycopyrrolate successfully treated intraoperative penile erection. The physiology and pharmacology of erection are reviewed, and pharmacologic treatment options and surgical treatments are reviewed. Conclusions: In patients with coronary artery disease, or in situations where cardiovascular stability is desired, glycopyrrolate is an effective means of relieving intraoperative penile erections. Other pharmacologic interventions, based on the physiology of erections, are presented. Nitric oxide, a potent smooth muscle relaxant, has been shown to be involved in the initiation and maintenance of erections; future research involving specific inhibitors of this chemical is indicated for the possible treatment of intraoperative penile erections.